2015
DOI: 10.1186/s40781-015-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of linkage disequilibrium levels in Iranian indigenous cattle using whole genome SNPs data

Abstract: BackgroundKnowledge of linkage disequilibrium (LD) levels among different populations can be used to detect genetic diversity and to investigate the historical changes in population sizes. Availability of large numbers of SNP through new sequencing technologies has provided opportunities for extensive researches in quantifying LD patterns in cattle breeds. The aim of this study was to compare the extent of linkage disequilibrium among Iranian cattle breeds using high density SNP genotyping data.ResultsA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…However, Gautier et al (2007) and Khatkar et al (2008) suggested that 75,000 to 300,000 SNPs would be required for association mapping studies within worldwide cattle breeds, which is in agreement with the density suggested in the present study for American mink. For instance, similar to our results, r 2 > 0.3 extended up to distances of 10-20 kb in Nguni and Drakensberger cattle breeds of South Africa (Makina et al, 2015) and several cattle breeds of Iran (Karimi et al, 2015). In addition, short extensions of LD (average r 2 > 0.3 at distances of >20 kb) were reported at some breeds of sheep (Kijas et al, 2014;Chitneedi et al, 2017;Liu et al, 2017), pig (Amaral et al, 2008;Ai et al, 2013), and domestic cats (Alhaddad et al, 2013), which are comparable to the ranges obtained in our study.…”
Section: Discussionsupporting
confidence: 91%
“…However, Gautier et al (2007) and Khatkar et al (2008) suggested that 75,000 to 300,000 SNPs would be required for association mapping studies within worldwide cattle breeds, which is in agreement with the density suggested in the present study for American mink. For instance, similar to our results, r 2 > 0.3 extended up to distances of 10-20 kb in Nguni and Drakensberger cattle breeds of South Africa (Makina et al, 2015) and several cattle breeds of Iran (Karimi et al, 2015). In addition, short extensions of LD (average r 2 > 0.3 at distances of >20 kb) were reported at some breeds of sheep (Kijas et al, 2014;Chitneedi et al, 2017;Liu et al, 2017), pig (Amaral et al, 2008;Ai et al, 2013), and domestic cats (Alhaddad et al, 2013), which are comparable to the ranges obtained in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Minor allele frequency varied between breeds, ranging from 0.23 (Kangayam) to 0.26 (Vechur), with an average observed heterozygosity of 0.35 in all samples examined (Table 1). The similar estimates of MAF were also reported in Nellore, Holstein, Iranian, Ethiopian and South African cattle [22][23][24][25][26] , which varied from 0.21 to 0.25 in Bos indicus and Bos Taurus cattle breeds. However, higher/lower estimates were also reported in other cattle breeds [27][28][29] .…”
Section: Resultssupporting
confidence: 80%
“…The LD between markers provides insight in exploring the level of diversity between different breeds, inferring the frequency of recombination events, investigating the change in effective population size across generations, and identifying genomic regions to improve economically important traits [ 1 3 ]. The pattern of LD is mainly determined by the physical distance between markers, although several other demographic and evolutionary factors including population stratification, inbreeding, effective population size, genetic bottleneck, genetic drift, migration, mutation, selection, and recombination rate may also influence the extent and pattern of LD [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%